EXTERNAL CHARACTERISATION OF PEELED VENEER FROM SOME PLANTATION SPECIES IN VIETNAM - Manh Tuong, Vu; Hien Mai, Trinh (Journal of Forestry Science and Technology, 2019)
Three Vietnamese plantation species Acacia mangium, Acacia hybrid (A. mangium x A. auriculiformis) and Eucalyptus urophylla in total nine sites (three sites per species) were chosen for this study. Each site had a different silvicultural or age regime and meet the requirements for veneer production. The largest trees in each site were harvested for peeled veneer trials with the veneer sheet dimensions were 2.8 mm thick × 1300 mm (same as log length) × 800 mm, then the veneer sheets were dried to a moisture content of 10% before assessment of knot and split characterisation and quality grading. The research results indicated that: The average number of knots in veneer sheet measured for each species tends to decrease with increasing age. The older E. urophylla plantations produced veneer with the least number of average knots, followed by A. mangium and then Acacia hybrid. Acacia hybrid produced higher levels of large knots (> 3 cm) compared to the other species investigated. The average number of end splits for the acacia species reduced with age but progressively increased with age for E. urophylla. The percentage of veneer affected by end split was lowest for the oldest A. mangium and E. urophylla plantations tested. The veneer grading was performed in accordance with Australian and New Zealand Standard AS/NZS 2269.0:2012. Loose and sound knots were the main reasons for preventing veneers achieving a grade quality higher than D-grade. Other defects common across all species and contributing to preventing veneers from attaining higher grades than D-grade are cumulative defects, resource holes, grain breakout and roughness. The latter two are considered manufacturing defects and therefore there is great opportunity to further optimise the process through the introduction of billet conditioning (steaming or boiling), lathe setup etc. to reduce these defects.